MODEL-MODEL PENGEMBANGAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH/PERGURUAN TINGGI - Nurlaila Nurlaila (Ta'dib: Jurnal Pendidikan Islam, 2011)
Islamic religious education quality improvement is expected to resolve the multidimensional crisis in our country, especially the moral-ethical aspects, and also be able to contribute in elaborating the meaning of national education that serves to develop skills and build character and civilization of the nation's dignity in the context of the intellectual life of the nation that aims for the development of potential learners in order to become a man of faith, fear of God Almighty, noble, healthy, knowledgeable, capable, creative, independent, and become citizens of a democratic and responsible. Developing models of PAI in Schools / Colleges General include: Model dichotomous, Mechanism Model, Model Organism / Systemic, and the Integrative Education Model. Teraebut models needed to overhaul capabilities and political well from policy makers, especially the leaders of the institution itself.